Workload Measurement Models In Hospital: Literature Review - Susilawati, Yeni; Komariah, Maria; Somantri, Irman (Publikasi Indonesia, 2023)
Nurse workload is all activities, activities, actions taken by a nurse while the nurse is on duty in a hospital service unit. The purpose of this literature is to identify which method is more effective and efficient to measure the workload of nurses. Article review was carried out through several electronic databases including Google Scholar, Google Scholar, Pubmed with the keyword